Update and optimal use of a brinzolamide-timolol fixed combination in open-angle glaucoma and ocular hypertension - Syed MF (Dove Medical Press, 2011)
Misha F Syed, Emma KR LoucksDepartment of Ophthalmology and Visual Sciences, The University of Texas Medical Branch, Galveston, TX, USAAbstract: Glaucoma encompasses a wide clinical spectrum of disease, with the common pathophysiology of progressive optic neuropathy leading to visual field loss. Elevated intraocular pressure (IOP) is a key risk factor in disease progression. Treatment is aimed at reduction of IOP to minimize continued optic nerve head damage. Pharmacologic treatment with various classes of IOP-lowering medications is generally employed before more aggressive surgical interventions. Monotherapy is generally accepted as initial therapy for glaucoma, but at least half of patients may require more than one IOP-lowering medication. One option is the fixed combination of brinzolamide 1% and timolol maleate 0.5%, which is commercially available in some countries as Azarga® for treatment of glaucoma not adequately responsive to monotherapy. These agents may also be used in an unfixed fashion, but fixed combination therapy is generally more convenient for patients, which may result in improved compliance, a reduction of the "washout effect" from instilling multiple drops, and a potential reduction in the side effects related to multiple doses of preservatives.Keywords: brinzolamide, timolol, glaucoma, fixed combination therapy, ocular hypertension